Fe-based alloy powder and mixed powder
Patent Information
- Application Number
- JP2025062141
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Filing Date
- 2025-04-03
- Publication Date
- 2026-10-16
Smart Images

Figure 2026168753000001_ABST
Abstract
Description
[Technical Field]
[0001] The present invention relates to Fe-based alloy powders and mixed powders, and more particularly to Fe-based alloy powders suitable as matrix materials for sintered valve seats, and mixed powders containing the same. [Background technology]
[0002] The valve seats in automobile engines are subjected to high loads and wear due to repeated contact with the valves during operation. Therefore, high wear resistance is required for the contact surface of the valve seat with the valve. Furthermore, valve seats are required to suppress the rise in valve temperature. For this reason, valve seats are sometimes made with a two-layer structure, using a high thermal conductivity material for the layer in contact with the cylinder (hereinafter also called the "support layer") and a high wear-resistant material for the layer in contact with the valve (hereinafter also called the "seat layer").
[0003] Traditionally, valve seat layers were manufactured by press-molding and sintering a mixed powder of iron powder (matrix material) and hard particles. Furthermore, to further improve the wear resistance of the seat layer, all or part of the iron powder was sometimes replaced with a harder Fe-based alloy powder. In particular, SKH51 (Fe-0.8C-4Cr-5Mo-6W-2V), a type of high-speed steel, is an Fe-based alloy containing a hard phase mainly composed of metal carbides, and is widely used as a matrix material for seat layers.
[0004] Various proposals have been made regarding sintered valve seats manufactured using such powder metallurgy methods, and the materials for manufacturing them. For example, Patent Document 1 discloses a mixed powder for manufacturing a valve seat sheet layer, comprising iron powder, high-speed steel powder, graphite powder, Co powder, Ni powder, Co-based intermetallic compound powder (hard particles), MnS powder, and zinc stearate powder. The document states that dispersing hard particles in the matrix phase of the valve seat layer significantly improves the wear resistance of the valve seat.
[0005] Patent Document 2 contains: (a) A mixed powder of high-speed steel powder and hard particles made of a Co-based alloy is formed, (b) A ring made of Cu-Fe-Mn alloy is placed on top of the compacted powder. (c) In this state, bake the compacted powder at 1150°C. A sheet layer of a sintered valve seat obtained by this method is disclosed.
[0006] The document states: (A) By this method, a sheet layer can be obtained in which Cu alloy is dissolved into the voids of the sintered body, and (B) By using only high-speed steel powder instead of pure iron powder in the matrix, dispersing hard particles made of Co-based alloy in the matrix, and dissolving Cu alloy into the voids of the sintered body, the wear resistance of the sheet layer in a high exhaust temperature environment is improved. It is stated.
[0007] When fuel is burned in the combustion chamber, soot is generated, and some of it adheres to the surface of the valve seat. The soot adhering to the valve seat surface acts as a lubricant, suppressing wear that occurs when it comes into contact with the valve. However, with the recent advancements in lean-burn combustion, the amount of soot generated during combustion has decreased, and the amount of valve seat wear is tending to increase.
[0008] To solve this problem, as described in Patent Documents 1 and 2, all or part of the pure iron powder used to form the matrix of the sheet layer is replaced with high-speed steel powder to increase the hardness of the matrix. However, since high-speed steel powder immediately after production by the atomization method is highly hard, a high compaction density cannot be obtained by simply compacting it. In order to obtain a high compaction density, it was necessary to soften the high-speed steel powder by subjecting it to a spheroidizing heat treatment at a high temperature (approximately 1060°C) for a long period of time (7 days).
[0009] High-temperature and long-time heat treatment of high-speed steel powder contributes to increasing the cost of sintered valve seats. In addition, since a large amount of energy is consumed in the heat treatment process, it also leads to an increase in CO2 emissions. Furthermore, when high-speed steel powder is subjected to high-temperature heat treatment for a long time, part of the powder melts, so that when the powder is cooled to room temperature, the particles are in a welded state. Therefore, the high-speed steel powder after heat treatment cannot be directly used for manufacturing sintered valve seats. To use the heat-treated high-speed steel powder for manufacturing sintered valve seats, it is necessary to crush the heat-treated high-speed steel powder, and the crushing treatment also contributes to increasing the cost of sintered valve seats. [Prior Art Documents] [Patent Documents]
[0010] [Patent Document 1] Japanese Patent No. 6265474 [Patent Document 2] Japanese Unexamined Patent Application Publication No. 2022-050275 [Summary of the Invention] [Problem to be Solved by the Invention]
[0011] The problem to be solved by the present invention is to provide an Fe-based alloy powder that allows long-time heat treatment and crushing treatment to be omitted without significantly impairing powder characteristics and sintering characteristics, and that enables production of a high-hardness sintered body. Another problem to be solved by the present invention is to provide a mixed powder that contains such an Fe-based alloy powder and is suitable as a material for manufacturing sintered valve seats. [Means for Solving the Problems]
[0012] In order to solve the above problems, the Fe-based alloy powder according to the present invention is C≦0.04mass%, 0.3≦Si≦1.5mass%, 2.5 ≤ Cr ≤ 13.5 mass%, 0.4 ≤ Mo ≤ 10.0 mass%, 0 ≤ W ≤ 10.0 mass%, 0.3 ≤ V ≤ 3.4 mass%, and, 0 ≤ Co ≤ 10.0 mass% It contains, with the remainder consisting of Fe and unavoidable impurities. Average particle size D 50 The size is between 20 μm and 50 μm. The average circularity is between 0.6 and 0.8.
[0013] however, "Average particle size D" 50 " refers to the median diameter in the number-based cumulative particle size distribution measured using laser diffraction scattering. The aforementioned "average circularity" refers to the particle size (equivalent diameter of a circle) being the average particle size D 50 This refers to the arithmetic mean of the circularity e measured for a total of 11 particles, each measuring ±iμm (where i is an integer between 0 and 5). The aforementioned "circularity e" refers to the value expressed by the following formula (1).
[0014] e = 4πS / L 2 …(1) however, S is the area of the particle image when the particle is observed under a microscope. L is the perimeter of the particle image.
[0015] The mixed powder according to the present invention is Fe-based alloy powder according to the present invention, Graphite powder and Hard particles made of a material having a higher hardness than the aforementioned Fe-based alloy powder, Lubricant and Includes, The amount of graphite powder added is between 0.30 mass% and 2.1 mass%. However, the "amount of graphite powder added" refers to the ratio of the mass of the graphite powder to the total mass of the Fe-based alloy powder and the graphite powder. [Effects of the Invention]
[0016] When a molten metal containing a predetermined amount of alloying elements and low carbon content is atomized using a water atomization method, optimizing the manufacturing conditions yields an Fe-based alloy powder with an average particle size and average circularity suitable for compaction. Because the Fe-based alloy powder thus obtained has low carbon content, it has low hardness and does not require spheroidizing heat treatment or crushing treatment. Therefore, the powder can be compacted directly immediately after manufacturing. Furthermore, because the Fe-based alloy powder obtained in this way has good formability, sintered bodies using it exhibit high sintering density.
[0017] When an appropriate amount of graphite powder and hard particles are added to the Fe-based alloy powder according to the present invention and mixed, and the mixed powder is molded and sintered, a sintered body is obtained in which hard particles are dispersed in a matrix made of Fe-based alloy. Moreover, during sintering, carbon diffuses into the low-C Fe-based alloy matrix, and metal carbides precipitate in the matrix. The sintered body obtained in this way is not only high-density but also exhibits high hardness because the hard particles are dispersed in a high-hardness matrix. Therefore, the sintered body exhibits high wear resistance. [Brief explanation of the drawing]
[0018] [Figure 1] This is a schematic diagram of a valve seat wear testing machine. [Figure 2] This is an explanatory diagram to illustrate the wear locations on a wear test specimen. [Figure 3] This is an SEM image of a cross-section of the matrix sintered body obtained in Example 1. [Figure 4] This is an SEM image of the cross-section of the matrix sintered body obtained in Comparative Example 1. [Figure 5] This is an SEM image of a cross-section of the matrix sintered body obtained in Comparative Example 12. [Figure 6] This is an SEM image of the Fe-based alloy powder obtained in Example 22. [Figure 7] This is an SEM image of the Fe-based alloy powder obtained in Comparative Example 15. [Modes for carrying out the invention]
[0019] One embodiment of the present invention will be described in detail below. [1. Fe-based alloy powder] [1.1. Ingredients] The Fe-based alloy powder according to the present invention (hereinafter also simply referred to as "powder") contains the following elements, with the remainder consisting of Fe and unavoidable impurities. The types of added elements, their component ranges, and the reasons for their limitations are as follows.
[0020] (1) C ≤ 0.04 mass %: Carbon (C) is an element that causes metal carbides to form in the powder, increasing its hardness. Therefore, if the amount of C is excessive, the powder becomes excessively hard, and a high compaction density may not be obtained when the powder is press-molded. Accordingly, the amount of C needs to be 0.04 mass% or less. Preferably, the amount of C is 0.01 mass% or less. A lower C content is preferable. However, excessive reduction of the C content leads to increased manufacturing costs. Therefore, a C content of 0.002 mass% or more is preferable. A C content of 0.005 mass% or more is even more preferable.
[0021] (2) 0.3 ≤ Si ≤ 1.5 mass %: Si is an element that reduces the oxygen concentration in the molten metal when dissolved in air. If the amount of Si becomes too low, the oxygen concentration in the molten metal will increase when dissolved in air, and consequently, the oxygen concentration in the powder will also increase. Powder with a high oxygen concentration has poor moldability, and even if it is press-molded, a high compaction density cannot be obtained. A decrease in compaction density leads to a decrease in sintering density, which reduces the wear resistance of the sintered body. Furthermore, when manufacturing a sintered body using a mixed powder of Fe-based alloy powder and graphite powder (hereinafter also simply referred to as "mixed powder"), Si is an element that forms silicides and increases the hardness of the sintered body. If the amount of Si is too low, the hardness of the sintered body may become excessively low. Therefore, the amount of Si needs to be 0.3 mass% or more. Preferably, the amount of Si is 0.6 mass% or more.
[0022] On the other hand, if the Si content is excessive, the hardness of the powder may become excessively high, reducing its moldability. This decrease in moldability leads to a reduction in sintering density, which in turn reduces the wear resistance of the sintered body. Therefore, the Si content must be 1.5 mass% or less. Preferably, the Si content is 0.9 mass% or less.
[0023] (3) 2.5 ≤ Cr ≤ 13.5 mass%: Cr is an element that improves the oxidation resistance and heat resistance of powder and sintered bodies manufactured using it. If the amount of Cr becomes too low, the oxidation resistance and heat resistance of the sintered body will decrease, which may lead to a decrease in the wear resistance of the sintered body. Furthermore, when manufacturing sintered bodies using mixed powders, Cr is an element that forms carbides and increases the hardness of the sintered body. If the amount of Cr becomes too low, the hardness of the sintered body may become excessively low. Therefore, the amount of Cr must be 2.5 mass% or more.
[0024] On the other hand, if the amount of chromium (Cr) is excessive, the hardness of the powder may become excessively high, reducing its moldability. This decrease in moldability leads to a reduction in sintering density, which in turn reduces the wear resistance of the sintered body. Therefore, the amount of Cr should be 13.5 mass% or less.
[0025] (4) 0.4 ≤ Mo ≤ 10.0 mass%: Mo is an element that improves the heat resistance of powder and sintered bodies manufactured using it. If the amount of Mo becomes too low, the heat resistance of the sintered body will decrease, which may lead to a decrease in the wear resistance of the sintered body. Furthermore, when manufacturing sintered bodies using mixed powders, Mo is an element that forms carbides and increases the hardness of the sintered body. If the amount of Mo is too low, the hardness of the sintered body may become excessively low. Therefore, the amount of Mo needs to be 0.4 mass% or more.
[0026] On the other hand, if the amount of Mo is excessive, the hardness of the powder may become excessively high, which can reduce its moldability. This decrease in moldability leads to a reduction in sintering density and a decrease in the wear resistance of the sintered body. Therefore, the amount of Mo needs to be 10.0 mass% or less.
[0027] (5) 0 ≤ W ≤ 10.0 mass%: In this invention, W is an optional element and can be added as needed. When manufacturing a sintered body using a mixed powder, W is an element that forms carbides and increases the hardness of the sintered body. If the amount of W is too low, the hardness of the sintered body may become excessively low. Therefore, the amount of W is preferably 1.0 mass% or more.
[0028] On the other hand, if the amount of W is excessive, the hardness of the powder may become excessively high, which can reduce its moldability. This decrease in moldability leads to a reduction in sintering density and a decrease in the wear resistance of the sintered body. Therefore, the amount of W needs to be 10.0 mass% or less.
[0029] (6) 0.3 ≤ V ≤ 3.4 mass%: When manufacturing a sintered body using a mixed powder, V is an element that forms carbides and increases the hardness of the sintered body. If the amount of V is too low, the hardness of the sintered body may become excessively low. Therefore, the amount of V needs to be 0.3 mass% or more.
[0030] On the other hand, if the amount of V is excessive, the hardness of the powder may become excessively high, which can reduce its moldability. This decrease in moldability leads to a reduction in sintering density and a decrease in the wear resistance of the sintered body. Therefore, the amount of V needs to be 3.4 mass% or less.
[0031] (7) 0 ≤ Co ≤ 10.0 mass %: In this invention, Co is an optional element and can be added as needed. When manufacturing a sintered body using a mixed powder, Co is an element that forms carbides and increases the hardness of the sintered body. If the amount of Co is too low, the hardness of the sintered body may become excessively low. Therefore, the amount of Co is preferably 1.0 mass% or more.
[0032] On the other hand, if the amount of Co is excessive, the hardness of the powder may become excessively high, reducing its moldability. This decrease in moldability leads to a reduction in sintering density, which in turn reduces the wear resistance of the sintered body. Therefore, the amount of Co needs to be 10.0 mass% or less.
[0033] (8) 0.002 ≤ P ≤ 0.6 mass%: In this invention, P is an optional element and can be added as needed. Low-carbon Fe-based alloy powders have lower sinterability compared to high-carbon Fe-based alloy powders. Adding an appropriate amount of phosphorus (P) to such low-carbon Fe-based alloy powders facilitates the formation of a liquid phase during sintering. As a result, liquid-phase sintering is promoted, making it easier to obtain a high-density sintered body. To obtain this effect, the amount of P is preferably 0.002 mass% or more.
[0034] On the other hand, if the amount of phosphorus (P) is excessive, an excessive liquid phase may be generated during sintering, making it difficult to maintain the shape of the sintered body. Therefore, the amount of phosphorus is preferably 0.6 mass% or less.
[0035] (9) Inevitable impurities: "Unavoidable impurities" refer to components that are mixed in during the industrial production of the Fe-based alloy powder according to the present invention due to various factors such as raw materials and manufacturing processes, and whose content is within a range that does not adversely affect the properties of the powder.
[0036] In the Fe-based alloy powder according to the present invention, the following components may be present in the amounts shown below. In such cases, these components are treated as unavoidable impurities in the present invention. O≦0.30mass%, N≦0.10mass%, S≦0.02mass%, Cu≦0.2mass%, Mn≦0.3mass%.
[0037] [1.2. Average Particle Diameter] The "average particle diameter D of the Fe-based alloy powder 50 " refers to the median diameter in the number-based cumulative particle size distribution measured using a laser diffraction scattering method. The same applies to the average particle diameters of graphite powder, hard particles, and flow aid described later.
[0038] The average particle diameter D of the Fe-based alloy powder 50 affects the flowability and sinterability of the powder. If D 50 is too small, the flowability of the powder may decrease. Therefore, D 50 needs to be 20μm or more. D 50 is preferably 25μm or more. Since the Fe-based alloy according to the present invention has a low C content, it has lower sinterability than high-C Fe-based alloy powders (for example, high-speed steel powder). Therefore, if D 50 is too large, the density of the sintered body may decrease excessively. Therefore, D 50 needs to be 50μm or less. D 50 is preferably 47μm or less.
[0039] [1.3. Average Circularity] "Average circularity" refers to the arithmetic mean of the circularity e measured for a total of 11 particles whose particle diameter (equivalent circle diameter) is within the range of average particle diameter D 50 ±iμm (i is an integer of 0 to 5). Here, D 50 represents the average particle diameter of the powder measured by a laser diffraction scattering method. The particles used for calculating the average circularity can be arbitrarily selected from particles that satisfy the particle diameter condition. Further, it is preferable to use a dynamic image analysis method for measuring the circularity.
[0040] "Circularity e" refers to the value represented by the following formula (1). e=4πS / L 2 …(1) Provided that S is the area of the particle image when the particle is observed under a microscope. L is the perimeter of the particle image. If the particle image is a perfect circle, the circularity e is 1.0.
[0041] Average circularity affects the flowability of the powder and the strength of the molded product. If the average circularity becomes too small, the flowability of the powder may decrease excessively. Therefore, the average circularity should be 0.6 or higher. On the other hand, if the average circularity becomes too large, the entanglement of particles during press molding decreases, leading to a reduction in the strength of the molded product. As a result, the molded product may collapse during handling. Therefore, the average circularity needs to be 0.8 or less.
[0042] [1.4. Usage] The Fe-based alloy powder according to the present invention has high formability due to its optimized hardness, average particle size, and average circularity. Moreover, it does not require high-temperature, long-duration heat treatment to achieve high formability. Furthermore, when producing a sintered body using the Fe-based alloy powder according to the present invention, optimizing the manufacturing conditions allows for the production of a sintered body with high hardness and high density. For this reason, the Fe-based alloy powder according to the present invention is suitable as a matrix material for a sintered valve seat comprising a matrix and hard particles dispersed within the matrix.
[0043] [2. Method for producing Fe-based alloy powder] The Fe-based alloy powder according to the present invention is Dissolve the raw materials that have been formulated to have the specified components, Atomize the molten metal. It can be manufactured by doing so.
[0044] [2.1. Preparation of molten metal] First, the raw materials, which have been formulated to have the specified components, are dissolved to obtain a molten metal. The method of dissolving the raw materials is not particularly limited, and the most suitable method can be selected according to the purpose. The method for dissolving the raw materials is: (a) an atmospheric dissolution method in which raw materials are dissolved in the atmosphere, (b) Atmospheric dissolution method in which raw materials are dissolved in an inert gas atmosphere such as N2 or Ar. They can be broadly categorized into these two groups. To produce the powder at a low cost, it is preferable to use the atmospheric dissolution method.
[0045] [2.2. Atomizing the molten metal] Next, the molten metal is atomized. The atomization method is as follows: (a) Water atomization method in which water is sprayed onto molten metal, (b) Gas atomization method in which an inert gas is blown onto the molten metal. They can be broadly categorized into these two groups. To obtain a powder with a moderately low average circularity, it is preferable to use the water atomization method.
[0046] [3. Mixed powder] The mixed powder according to the present invention is Fe-based alloy powder according to the present invention, Graphite powder and Hard particles made of a material having a higher hardness than the aforementioned Fe-based alloy powder, Lubricant and Includes. The mixed powder may also contain a fluidizing agent.
[0047] [3.1. Ingredients] [3.1.1. Fe-based alloy powder] Details regarding the Fe-based alloy powder are as described above, so we will omit further explanation.
[0048] [3.1.2. Graphite powder] The Fe-based alloy powder according to the present invention has a lower carbon content compared to high-speed steel powder, resulting in good formability, but the hardness of the sintered body tends to decrease. Graphite powder is used to supply carbon to the Fe-based alloy powder during sintering, generating metal carbides in the matrix and increasing the hardness of the matrix.
[0049] Average particle size of graphite powder D 50This is not particularly limited, and the optimal value can be selected according to the purpose. D of graphite powder 50 If the size becomes too small, the fluidity of the mixed powder may decrease excessively. Therefore, the D of graphite powder 50 The particle size is preferably 10 μm or larger. On the other hand, D of graphite powder 50 If the size becomes too large, the moldability may decrease. Therefore, the D of graphite powder 50 The particle size is preferably 30 μm or less.
[0050] [3.1.3. Hard particles] "Hard particles" refer to particles made of a material having a higher hardness than the Fe-based alloy powder. In particular, the hard particles are preferably made of a material having a higher hardness than the alloy obtained by increasing the carbon content of the Fe-based alloy powder according to the present invention to 0.8 mass% or more. Hard particles are used to increase the hardness of a sintered body by dispersing them in a matrix made of Fe-based alloy, thereby improving the wear resistance of the sintered body. The material of the hard particles is not particularly limited, as long as it performs this function.
[0051] Examples of hard particle materials include, (a)Co-28Mo-8Cr-2.5Si alloy (DAPSKMC400), (b) Co-30Cr-4~15W alloy (Stellite®), (c)Co-28Mo-18Cr-3.4Si alloy (DAPSKMC800), (d) Examples include Co-22Mo-18Cr-16Ni-2.7Si alloy (DAPSKMC900).
[0052] Average particle size D of hard particles 50 This is not particularly limited, and the optimal value can be selected according to the purpose. D of hard particles 50 If the hard particle size becomes too small, the components contained in the hard particle diffuse into the matrix, reducing the particle size of the hard particle and potentially causing it to cease functioning as a hard particle. Therefore, the D of the hard particle 50 The particle size is preferably 30 μm or larger. On the other hand, hard particles D 50 If it becomes too large, the moldability may decrease. Therefore, D 50 The particle size is preferably 80 μm or less.
[0053] [3.1.4. Lubricants] Lubricants are used to reduce friction between particles and improve moldability when molding mixed powders. The materials of the lubricant are not particularly limited as long as they perform this function. Examples of lubricants include stearic acid, zinc stearate, aluminum stearate, calcium stearate, and ethylenebisamide (EBS).
[0054] [3.1.5. Fluid-enhancing agents] The mixed powder may further contain a flow aid in addition to the powders described above. If the mixed powder further contains a flow aid, the fluidity of the mixed powder will be further improved. The material of the flow aid is not particularly limited as long as it performs the function described above. Examples of flow aids include silica, magnesium aluminometasilicate, talc, TiO2, MgO, and Al2O3. Silica powder with an average particle size on the order of nanometers (nanosilica powder) is particularly preferred as the flow aid.
[0055] Average particle size D of the flow aid 50 This is not particularly limited, and the optimal value can be selected according to the purpose. D of the fluidity aid 50 If the amount becomes too small, the fluidity improvement effect may not be obtained. Therefore, the D of the fluidity aid 50 The wavelength is preferably 6 nm or greater. On the other hand, the liquid additive D 50 If the amount becomes too large, the density of the sintered body may decrease. Therefore, the amount of the flow aid D 50 The wavelength is preferably 30 nm or less.
[0056] [3.2. Amount added] [3.2.1. Amount of graphite powder to add] "Amount of graphite powder added" refers to the ratio of the mass of graphite powder to the total mass of Fe-based alloy powder and graphite powder.
[0057] As mentioned above, graphite powder is used to supply carbon to low-carbon Fe-based alloy powder and to generate metal carbides. Therefore, if the amount of graphite powder added is too small, the hardness of the sintered body may decrease. Accordingly, the amount of graphite powder added needs to be 0.30 mass% or more. Preferably, the amount added is 0.50 mass% or more.
[0058] On the other hand, if the amount of graphite powder added is excessive, the sintering density may decrease excessively when a sintered body is manufactured using the mixed powder, and the wear resistance of the sintered body may decrease. Therefore, the amount of graphite powder added must be 2.1 mass% or less. Preferably, the amount added is 2.0 mass% or less.
[0059] [3.2.2. Amount of hard particles added] "Amount of hard particles added" refers to the ratio of the mass of hard particles to the total mass of Fe-based alloy powder and hard particles.
[0060] If the amount of hard particles added is too low, the hardness of the sintered body may decrease when the mixed powder is used to manufacture the sintered body. Therefore, the amount of hard particles added is preferably 15.0 mass% or more. More preferably, the amount added is 20.0 mass% or more. On the other hand, if the amount of hard particles added is excessive, the toughness of the sintered body may decrease. Therefore, the amount of hard particles added is preferably 40.0 mass% or less. More preferably, the amount added is 30.0 mass% or less.
[0061] [3.2.3. Amount of lubricant to add] "Amount of lubricant added" refers to the mass of lubricant when the total mass of Fe-based alloy powder, graphite powder, and hard particles is set to 100.
[0062] If the amount of lubricant added is too small, the compaction density of the molded product may become excessively low. Therefore, it is preferable to add 0.4 parts by mass or more of lubricant. On the other hand, if the amount of lubricant added is excessive, the sintering density may decrease excessively when a sintered body is made using the mixed powder. Therefore, the amount of lubricant added is preferably 1.6 parts by mass or less.
[0063] [3.2.4. Amount of fluidizing agent to be added] "Amount of fluidizing agent added" refers to the ratio of the mass of the fluidizing agent to the total mass of the mixed powder.
[0064] If the amount of fluidizing agent added is too small, the effect of improving the fluidity of the mixed powder may not be obtained. Therefore, it is preferable to add 0.05 mass% or more of the fluidizing agent. On the other hand, if the amount of fluidizing agent added is excessive, the fluidizing agent may aggregate when a sintered body is made using the mixed powder, resulting in large defects. Therefore, it is preferable to add 0.5 mass% or less of the fluidizing agent.
[0065] [3.3. Usage] The mixed powder according to the present invention consists of a highly formable Fe-based alloy powder to which an appropriate amount of graphite powder and hard particles are added. When a sintered body is made using this, a sintered body with high hardness and high density can be obtained. For this reason, the mixed powder according to the present invention is suitable as a material for a sintered valve seat comprising a matrix and hard particles dispersed within the matrix.
[0066] [4. Effect] When molten metal, whose composition has been adjusted to produce high-speed steel powder, is sprayed using the water atomization method, optimizing the spraying conditions yields powder with an average particle size and average circularity suitable for compaction. However, because the high-speed steel powder obtained in this way is highly hard, a high compaction density cannot be obtained by simply compacting it. To increase the compaction density, it was necessary to subject the high-speed steel powder immediately after production by the water atomization method to high-temperature, long-duration spheroidizing heat treatment and crushing treatment.
[0067] In contrast, when a molten metal containing a predetermined amount of alloying elements and low carbon content is atomized using a water atomization method, optimizing the manufacturing conditions yields an Fe-based alloy powder with an average particle size and average circularity suitable for compaction molding. The Fe-based alloy powder obtained in this way has low hardness due to its low carbon content and does not require spheroidizing heat treatment or crushing treatment. Therefore, the powder can be compacted directly immediately after manufacturing. Furthermore, because the Fe-based alloy powder obtained in this way has good moldability, molded bodies using it exhibit a high compaction density.
[0068] On the other hand, since the Fe-based alloy powder according to the present invention is low in carbon, a sintered body with high hardness cannot be obtained by sintering a compact containing only the Fe-based alloy powder. Furthermore, when the Fe-based alloy powder according to the present invention is mixed with hard particles, and the mixed powder is molded and sintered, the hardness of the sintered body becomes higher than that of a sintered body without hard particles. However, because the matrix has low hardness, there are limitations to improving wear resistance.
[0069] In contrast, when an appropriate amount of graphite powder and hard particles are added to the Fe-based alloy powder according to the present invention and mixed, and the mixed powder is molded and sintered, a sintered body is obtained in which hard particles are dispersed in a matrix made of Fe-based alloy. Moreover, during sintering, carbon diffuses into the low-C Fe-based alloy matrix, and metal carbides precipitate in the matrix. The sintered body obtained in this way is not only high-density, but also exhibits high hardness because hard particles are dispersed in a high-hardness matrix. Therefore, the obtained sintered body exhibits high wear resistance. [Examples]
[0070] (Examples 1-24, Comparative Examples 1-16) [1. Sample Preparation] [1.1. Preparation of Fe-based alloy powder] The raw materials, formulated to achieve the predetermined composition, were melted in a high-frequency induction furnace. The resulting molten metal was atomized to obtain powder. For Examples 1-24 and Comparative Examples 1-14 and 16, the water atomization method was used. For Comparative Example 15, the gas atomization method was used. Furthermore, Comparative Example 16 underwent spheroidizing heat treatment and crushing treatment after water atomization. The spheroidizing heat treatment conditions were a temperature of 1060°C and a holding time of 170 hours.
[0071] [1.2. Preparation of Matrix Sintered Bodies (Sintered Bodies that Do Not Contains Hard Particles)] Fe-based alloy powder and graphite powder were blended in a predetermined ratio to obtain a blended powder. The amount of graphite powder added was 0 to 2.3 mass%. 0.5 parts by mass of lubricant were added to 100 parts by mass of the blended powder and mixed to obtain a mixed powder. Zinc stearate was used as the lubricant.
[0072] The resulting mixed powder was molded at a pressure of 7 t / cm². 2 The powder was compacted to obtain a cylindrical compact with a diameter of 11 mm and a thickness of 10 mm. The cylindrical compact was degreased, and the degreased body was sintered to obtain a matrix sintered body. Degreasing was performed by heating the compact in air at 500°C for 1 hour. Sintering was performed by heating the degreased body in a decomposing ammonia atmosphere (N2 + 3H2) at 1250°C or 1160°C (only for samples with added phosphorus) for 1 hour.
[0073] [1.3. Preparation of sintered bodies for wear testing (sintered bodies containing hard particles)] A blended powder was obtained by mixing 69.2 parts by mass of Fe-based alloy powder, 30 parts by mass of hard particles, and a predetermined amount by mass of graphite powder. The amount of graphite powder added was set so that the "amount of graphite powder added (= ratio of the mass of graphite powder to the total mass of Fe-based alloy powder and graphite powder)" was 0 to 2.3 mass%. DAPSKMC400 (Co-28Mo-8Cr-2.5Si alloy) was used as the hard particles. A mixed powder was obtained by adding 0.8 parts by mass of lubricant to 100 parts by mass of the blended powder and mixing. Zinc stearate was used as the lubricant.
[0074] The resulting mixed powder was molded at a pressure of 7 t / cm². 2 The powder was compacted to obtain a disc-shaped compact with a diameter of 35 mm and a thickness of 14 mm. Subsequently, degreasing and sintering were performed in the same manner as for the matrix sintered body to obtain a disc-shaped sintered body for wear testing.
[0075] [2. Test Method] [2.1. Characterization of Fe-based alloy powders] [2.1.1. Average particle size] Using laser diffraction scattering, the particle size distribution and average particle size D of Fe-based alloy powder were determined. 50 The particle size distribution was measured using the Microtrac MT3300 series.
[0076] [2.1.2. Apparent density] The apparent density of Fe-based alloy powder was measured in accordance with JIS Z 2504-2021.
[0077] [2.1.3. Fluidity] The fluidity of Fe-based alloy powders was measured in accordance with JIS Z 2502-2021.
[0078] [2.1.4. Rattler Value] The Rattler values of Fe-based alloy powders were measured in accordance with JPMA P11.
[0079] [2.1.5. Mean Circularity] The circularity of Fe-based alloy powder was measured using dynamic image analysis. A powder shape analyzer (Microtrac, CAMSIZER X-2) was used to measure the circularity. The powder was sprayed dry, and the falling powder was photographed with a high-speed camera. The particle size (equivalent diameter) and circularity of each particle were measured by image processing. From the captured particle images, particles with a diameter of D 50 We selected a total of 11 particles with a radius of ±iμm (where i is an integer between 0 and 5), and calculated the arithmetic mean of their circularity.
[0080] [2.2. Characterization of Matrix Sintered Bodies] [2.2.1. Sintering density of matrix sintered body] The sintering density of the sintered body was measured in accordance with JIS Z 2501-2000.
[0081] [2.2.2. Vickers hardness of matrix sintered bodies] The Vickers hardness of the matrix sintered body was measured using a Vickers hardness tester. The load applied was 0.49 N.
[0082] [2.3. Characterization of abrasion test specimens] A wear resistance test of a sintered body for wear testing was performed using the valve seat wear testing machine shown in Figure 1 (hereinafter also simply referred to as the "wear testing machine"). First, a disc-shaped sintered body was processed into a valve seat shape to serve as the wear test piece. The wear test piece was set in the wear testing machine by press-fitting it into the seat holder. Furthermore, the wear resistance testing machine was driven under the conditions shown in Table 1, and the wear test piece was indirectly heated by heating the valve with a gas flame while the wear test piece was worn down by striking input from a crank drive.
[0083] [Table 1]
[0084] The shape of the abrasion test specimen was measured before and after the abrasion test using a shape measuring instrument. As shown in Figure 2 (enlarged view of the part indicated by arrow A in Figure 1), the difference D in the direction perpendicular to the surface of the abrasion test specimen was determined and this was defined as the amount of abrasion of the abrasion test specimen.
[0085] [3. Results] [3.1. Characterization of Matrix Sintered Bodies and Abrasion Test Specimens] Tables 2 and 3 show the composition of the Fe-based alloy powder, the properties of the matrix sintered body, and the wear test specimen. Figure 3 shows an SEM image of the cross-section of the matrix sintered body obtained in Example 1. Figure 4 shows an SEM image of the cross-section of the matrix sintered body obtained in Comparative Example 1. Figure 5 shows an SEM image of the cross-section of the matrix sintered body obtained in Comparative Example 12. From Tables 2-3 and Figures 3-5, the following can be seen.
[0086] (1) In Comparative Example 1, the wear amount of the abrasion test piece exceeded 20 μm. This is thought to be due to a low sintering density. See Figure 4. The low sintering density is thought to be because the powder hardness became excessively high due to an excess of carbon, resulting in reduced moldability. (2) Comparative Example 2 showed a wear amount exceeding 20 μm. This is thought to be due to a low sintering density. The low sintering density is thought to be because the low Si content resulted in a high oxygen concentration in the powder, leading to reduced moldability.
[0087] (3) Comparative Example 3 showed a wear amount exceeding 20 μm. This is thought to be due to the low hardness of the matrix (or sintered body). The low hardness of the matrix (or sintered body) is thought to be due to an excessively low amount of Cr. (4) Comparative Example 4 showed a wear amount exceeding 20 μm. This is thought to be due to the low hardness of the matrix (or sintered body). The decrease in the hardness of the matrix (or sintered body) is thought to be due to an excessively small amount of graphite powder being added.
[0088] (5) Comparative Example 5 showed a wear amount exceeding 20 μm. This is thought to be due to a low sintering density. The low sintering density is thought to be due to a decrease in the moldability of the powder because an excessive amount of graphite powder was added. (6) Comparative Example 6 showed a wear amount exceeding 20 μm. This is thought to be due to a low sintering density. The low sintering density is thought to be because the powder hardness became excessively high due to the excessive amount of Cr, resulting in a decrease in the moldability of the powder.
[0089] (7) Comparative Example 7 showed a wear amount exceeding 20 μm. This is thought to be due to a low sintering density. The low sintering density is thought to be because the excessive Si content resulted in excessively high powder hardness and reduced powder moldability. (8) Comparative Example 8 showed a wear amount exceeding 20 μm. This is thought to be due to a low sintering density. The decrease in sintering density is thought to be because the powder hardness became excessively high due to the excess Mo, resulting in a decrease in the moldability of the powder.
[0090] (9) Comparative Example 9 showed a wear amount exceeding 20 μm. This is thought to be due to a low sintering density. The low sintering density is thought to be because the amount of V was excessive, resulting in excessively high powder hardness and reduced powder moldability. (10) Comparative Example 10 showed a wear amount exceeding 20 μm. This is thought to be due to a low sintering density. The decrease in sintering density is thought to be because the excessive amount of W made the powder excessively hard, reducing the moldability of the powder.
[0091] (11) Comparative Example 11 showed a wear amount exceeding 20 μm. This is thought to be due to a low sintering density. The decrease in sintering density is thought to be because the powder hardness became excessively high due to the excessive amount of Co, resulting in a decrease in the moldability of the powder. (12) Comparative Example 12 could not be subjected to abrasion testing. This was because the excessive amount of P lowered the melting point of the matrix, resulting in the generation of a large amount of liquid phase during sintering, and consequently, the shape of the test specimen could not be maintained. See Figure 5.
[0092] (13) Comparative Example 13 showed a wear amount exceeding 20 μm. This is thought to be due to a low sintering density. The decrease in sintering density is thought to be due to a decrease in the moldability of the powder because the average particle size of the powder was excessively large. (14) Comparative Example 14 showed a wear amount exceeding 20 μm. This is thought to be due to a low sintering density. The decrease in sintering density is thought to be due to a decrease in powder fluidity and moldability because the average particle size of the powder was excessively small.
[0093] (15) Comparative Example 15 failed to produce a sintered body. This was because the average circularity of the powder was high and the powder shape was close to spherical, resulting in poor shape retention after molding and the molded body easily crumbled into powder. (16) Comparative Example 16 showed a wear amount exceeding 20 μm. This is thought to be due to a low sintering density. The low sintering density is thought to be because, after producing Fe-based alloy powder with a high carbon content, spheroidizing heat treatment was performed, but the hardness of the powder did not decrease sufficiently.
[0094] (17) Example 1 achieved a high sintering density despite not performing spheroidizing heat treatment after powder production. See Figure 3. This is thought to be because the amount of carbon in the Fe-based alloy powder was low, resulting in a moderately low powder hardness. In addition, because Example 1 had a high sintering density, the wear amount was 20 μm or less. (18) Examples 2 to 24 were similar, showing high sintering density and low wear.
[0095] [Table 2]
[0096] [Table 3]
[0097] [3.1. Characterization of Fe-based alloy powders] Table 4 shows the properties of the Fe-based alloy powder. Figure 6 shows an SEM image of the Fe-based alloy powder obtained in Example 22. Figure 7 shows an SEM image of the Fe-based alloy powder obtained in Comparative Example 15. From Table 4 and Figures 6-7, the following can be seen.
[0098] (1) Comparative Example 13 had a Rattler value exceeding 10. This is thought to be because the average particle size of the Fe-based alloy powder was too large. (2) Comparative Example 14 had a Rattler value exceeding 10. Also, Comparative Example 14 did not flow. This is thought to be because the average particle size of the Fe-based alloy powder was too small. (3) Comparative Example 15 had a Rattler value of 100%. This is thought to be because the average circularity was excessively large due to the production of the powder using the gas atomization method. See Figure 7. (4) Examples 1, 11, and 22 showed moderate fluidity and a low Rattler value. This is due to the average particle size D of the powder. 50 This is likely because the average circularity has been optimized. See Figure 6.
[0099] [Table 4]
[0100] Although embodiments of the present invention have been described in detail above, the present invention is not limited in any way to the above embodiments, and various modifications are possible without departing from the spirit of the present invention. [Industrial applicability]
[0101] The Fe-based alloy powder according to the present invention can be used as a matrix material for sintered valve seats.
Claims
1. C≦0.04mass%, 0.3≦Si≦1.5mass%, 2.5≦Cr≦13.5mass%, 0.4≦Mo≦10.0mass%, 0≦W≦10.0mass%, 0.3 ≤ V ≤ 3.4 mass%, and, 0≦Co≦10.0mass% It contains, with the remainder consisting of Fe and unavoidable impurities. Average particle size D 50 The size is between 20 μm and 50 μm. The average circularity is between 0.6 and 0.
8. Fe-based alloy powder. however, The above-mentioned “average particle size D 50 " refers to the median diameter in the number-based cumulative particle size distribution measured using laser diffraction scattering. The aforementioned "average circularity" refers to the particle size (equivalent diameter of a circle) being the average particle size D 50 This refers to the arithmetic mean of the circularity e measured for a total of 11 particles, each measuring ±iμm (where i is an integer between 0 and 5). The aforementioned "circularity e" refers to the value expressed by the following formula (1). e = 4πS / L 2 … (1) however, S is the area of the particle image when the particle is observed under a microscope. L is the perimeter of the particle image.
2. 0.002≦P≦0.6mass% The Fe-based alloy powder according to claim 1, further comprising:
3. The Fe-based alloy powder according to claim 1, used as a matrix material for a sintered valve seat comprising a matrix and hard particles dispersed within the matrix.
4. Fe-based alloy powder according to claim 1, Graphite powder and Hard particles made of a material having a higher hardness than the aforementioned Fe-based alloy powder, Lubricant and Includes, The amount of graphite powder added is 0.30 mass% or more and 2.1 mass% or less. Mixed powder. However, the "amount of graphite powder added" refers to the ratio of the mass of the graphite powder to the total mass of the Fe-based alloy powder and the graphite powder.
5. It further contains a fluidity enhancer, The amount of the aforementioned fluidizing agent added is 0.05 mass% or more and 0.5 mass% or less. The mixed powder according to claim 4. However, the "amount of fluidizing agent added" refers to the ratio of the mass of the fluidizing agent to the total mass of the mixed powder.
6. The mixed powder according to claim 4, used as a material for a sintered valve seat comprising a matrix and the hard particles dispersed within the matrix.
Citation Information
Patent Citations
Semiconductor device
JP1987065474A
Sintered valve seat
JP2022050275A